Assessment of the reproductive status of wild boar from hormonal estimation of faecal samples - Vashishat, Nisha; Kler, Tejdeep Kaur; Kumar, Manoj (Annals of Arid Zone, 2025)
Wild boar (Sus scrofa) population has increased constantly over the last three decades resulting into conflicts with the agro ecosystem. Damage to agricultural crops by wild boar is enormous and widespread. Therefore, understanding reproduction dynamics is necessary to control the local population successfully, which is of significant interest. One tool for evaluating reproductive functions in a wild population is to assess endocrine activity through hormone measurements in either blood, faeces, saliva, or other biological material. Endocrine analyses of steroid hormones enable us to evaluate reproductive status of animals; however, there is not much information available about sex hormone concentrations for the wild boar. The study involved a preliminary survey across different habitats during 2022-23 to estimate population of wild boar and variability in their reproductive hormone levels. Presence of wild boar was observed at village Ladhowal, Baranhara, Majarakalan, Rajjapur, Bhollewal, Dhanasu, Noorpur bet and Kharak of Ludhiana district of Punjab. Average herd size ranges from 5-9 individuals along the river Sutlej catchment areas where wild boars have ample habitat to roost in the day time and venture out during the night for feeding activities causing damage to agricultural crops. With the aim to study wild boar population with respect to their gender, faecal samples were collected from different habitats to analyse the reproductive hormones of wild boar. Results revealed distinct hormonal patterns corresponding to occurrence of male and female wild boars showing higher level of testosterone and progesterone during the months from July to December indicating more breeding activities as compared to from January to June. Non-invasive hormonal estimation of faecal samples may prove to be a valuable tool for monitoring the reproductive status of wild boar populations, offering a cost-effective and ethically sound alternative to traditional invasive methods. This approach, if thoroughly studied, could help in future wildlife management by guiding conservation efforts and population control tailored to wild boar reproductive dynamics across environments.